Knowledge about sexual transmitted disease (STDs) and risks involved amongst young people population living in south-eastern region of Poland - Puszkarz, Irena; Durnaś, Bonita; Król, Grzegorz; Bucki, Robert (Journal of Education, Health and Sport, 2017)
Introduction: Sexually transmitted diseases (STD) are considered to be a serious health matter with the numbers of cases continuously increasing. Numerous studies have pointed out that Polish youth do not have a sufficient knowledge of the risks involved with contracting STD, mainly because there are no effective sexual education within schools, families or medical institutions. Aim: The aim of this research was to investigate the level of knowledge concerning STD amongst the population of young adults between 19 and 24 years old living in the South-eastern region of Poland. Methods and Materials: The analysis was comprised of 104 people between 19-24 years old from which 57.7% were women and 42.3% were men. The method used to conduct described research was a diagnostic survey, from which a questionnaire created by the author was used alongside a Polish adaptation of the Multidimensional Health Locus of Control (MHLC). The analysis was carried out using Statistical 13 PL program. Results: More than half (54.8%) of those surveyed believed that STD contraction could only be possible via sexual intercourse. Amongst those surveyed the most known itemized STDs were HIV/AIDS (93.3%), genital herpes (86.5%), gonorrhoea (84.6%) and syphilis (80.8%). The knowledge of those surveyed was based on the information obtained through the internet (67.3%), leaflets and handouts (28.8%), television (22.1%) and lastly parents (1.9%). In the opinion of participating surveyed sexual education should come from a gynaecologist or sexual health professional (61.5%) or an experienced pedagogue (18.3%). There was no difference in STD knowledge between women and men (p>0.05). There was a significant difference in knowledge which was shown in the results of those surveyed between people with a basic and a higher education (p<0.05) with a statistically significant link between the ages of those surveyed and their knowledge (p<0.01). Conclusion: The knowledge of those surveyed is unsystematic and incomplete. Young people expect information from gynaecologist, sexual health professionals and experienced pedagogue. The subject of STD should be addressed more not only in schools but also within their own home whilst highlighting the importance of the role of the parents in this aspect. It is recommended to educate young people on where to obtain sufficient and adequate information from reliable sources.